Elevated Serum Levels of Soluble TNF Receptors and Adhesion Molecules Are Associated with Diabetic Retinopathy in Patients with Type-1 Diabetes. (3rd August 2015) - Sharma, Shruti; Purohit, Sharad; Sharma, Ashok; Hopkins, Diane; Steed, Leigh; Bode, Bruce; Anderson, Stephen W.; Caldwell, Ruth; She, Jin-Xiong
Abstract : Aims . To examine the association of the serum levels of TNF receptors, adhesion molecules, and inflammatory mediators with diabetic retinopathy (DR) in T1D patients. Methods . Using the multiplex immunoassay, we measured serum levels of eight proteins in 678 T1D subjects aged 20–75 years. Comparisons were made between 482 T1D patients with no complications and 196 T1D patients with DR. Results . The levels of sTNFR-I, sTNFR-II, CRP, SAA, sgp130, sIL6R, sVCAM1, and sICAM1 were significantly higher in the T1D patients with DR as compared to T1D patients with no complications. Multivariate logistic regression analysis revealed significant association for five proteins after adjustment for age, sex, and disease duration (sTNFR-I: OR = 1.57, sgp130: OR = 1.43, sVCAM1: OR = 1.27, sICAM1: OR = 1.42, and CRP: OR = 1.15 ). Conditional logistic regression on matched paired data revealed that subjects in the top quartile for sTNFR-I ( OR = 2.13 ), sTNFR-II ( OR = 1.66 ), sgp130 ( OR = 1.82 ), sIL6R ( OR = 1.75 ), sVCAM1 ( OR = 1.98 ), sICAM1 ( OR = 2.23 ), CRP ( OR = 2.40 ) and SAA ( OR = 2.03 ), had the highest odds of having DR. Conclusions . The circulating markers of inflammation, endothelial injury, and TNF signaling are significantly associated with DR in patients with T1D. TNFR-I and TNFR-II receptors are highly correlated, but DR associated more strongly with TNFR-I in these patients.